Factors Related to the Clinical Outcomes of the Kasai Procedure in Infants with Biliary Atresia - Mongkol Laohapensang; Patcharaphan Srikuancharoen; Niramol Tantemsapya (Siriraj Medical Journal, 2020)
Objective: The Kasai portoenterostomy has been accepted as the primary therapeutic treatment for biliary atresia. However, successful bile drainage does not always promise a long-term native liver survival. Several clinical factors were evaluated to discover associations with the outcomes. Methods: A retrospective chart review was conducted of infants with biliary atresia who underwent the conventional Kasai portoenterostomy at Siriraj Hospital, January 2006-August 2018. The patient demographics, perioperative clinical and laboratory data, adjuvant therapies, complications, and interventions were analyzed in correlation to the short- and long-term outcomes. The short-term outcome evaluated was the resolution of jaundice, while the long-term outcome was remaining jaundice-free with the native liver. Results: The complete medical records of 80 patients were retrospectively reviewed. Their mean age at the time of the Kasai portoenterostomies was 97 days. Overall, 66.3% achieved jaundice clearance. The mean follow-up duration was 50.5 months, with 51.3% of the patients remaining jaundice-free with their native liver. A prolonged duration of a prophylactic antibiotic was significantly related to the jaundice clearance, with a p-value of 0.002. Moreover, a lower number of episodes of cholangitis was significantly related to a good long-term outcome (p-value, 0.024). Conclusion: The prolonged provision of a prophylactic antibiotic as adjuvant therapy after the Kasai portoenterostomy was associated with jaundice clearance. An increased incidence of cholangitis episodes was associated with poor long-term outcomes. Postoperative adjuvant therapy should be standardized and maintained for the care of biliary atresia patients to improve their outcomes.